More Climate Finance for Sustainable Transport - Ebinger, Jane O.; Vandycke, Nancy; Rogers, John Allen (2015)
Actions to reduce greenhouse gas (GHG) emissions to stabilize warming at 2 degree Celsius, as agreed by the international community in 2009, will fall short if they do not include the transport sector. Transport is responsible for around 23 percent of global carbon dioxide emissions and emissions are expected to rise without further action to curb emission growth and invest in low carbon transport modes. Investment needs are estimated at around $3 trillion to increase the sustainability of existing and new transport systems and to mitigate climate change over the 2015-35 periods. This is in addition to existing annual investments estimated at $1-2 trillion. The actions taken today to send the right policy signals, and establish the enabling institutions and regulations to attract the necessary private finance will be critical to support this transformation. Significant investment opportunities exist in public transport systems, vehicle efficiency improvement, and reducing the need for travel through demand management, regional development policies, and land use planning. As the international community embarks on the road towards CoP 21 in Paris, there is a case to be made for more climate finance flowing towards transport.